Edema and features of optic nerve architecture in inflammatory and ischemic neuropathies. Clinical cases - N. M. Moyseyenko (Ukrainian Society of Ophthalmologists, 2024)
Purpose. To describe clinical cases of optic nerve edema in inflammatory and ischemic neuropathies and features of optic disc architecture revealed by optical coherence tomography. Methods. 4 patients were examined. Two patients were diagnosed with optic neuritis, and the other two with ischemic neuropathy. Ophthalmoscopically, signs of optic disc edema were found in all patients. Visometry, ophthalmoscopy, optical coherence tomography (OCT), and magnetic resonance imaging (MRI) were used. Result. Changes in the architecture of the optic nerve head were detected in cases of optic nerve edema in inflammatory (2 patients) and ischemic neuropathy (2 patients). In all examined patients, according to the conducted study, the results of OCT showed that optic nerve edema, except for case № 4, does not extend to the temporal segment of the head. In cases of inflammatory damage, cases 1 and 2, optic nerve atrophy was observed at later stages during repeated examinations. A light crescent zone is observed in the peripapillary area, which separates the temporal border of the optic nerve head (sectoral atrophy). Conclusion. Optic nerve edema in inflammatory and ischemic neuropathies is characterized by an increase in the thickness of the nerve fiber layers and a change in the configuration of the disk, which later transforms into segmental atrophy. The changes in the architecture of the optic disc were found to be the basis of diagnosis, monitoring, and evaluation of the effectiveness of treatment in acute optic neuropathies.